Ambivalensi Ekologis dan Rekontruksi Stewardship Berbasis Kalesang - Dian Felisia Nanlohy; Selvyen Sophia (DUNAMIS: Jurnal Teologi dan Pendidikan Kristiani, 2026)
Abstract. The ecological crisis in the Inner Ambon Bay reflects a deeper crisis of relationships, ethics, and the spirituality of the faith community. This research examines the ethical response of the GPM Lateri congregation to coastal degradation since 2004, highlighting the tension between confessional faith and everyday ecological practice. This qualitative study employs a contextual theological reflection framework grounded in a praxis-transformative model. Data were collected through interviews, observation, and document analysis, and were analysed thematically in dialogue with the concept of stewardship. The finding reveals the dominance of a “humans above nature” paradigm and a shallow ecological ethic. The article reconstructs stewardship through a dialogue between Humanity with Nature and the value of Kalesang, proposing a relational and contextual model of ecotheology for Indonesia’s urban coastal communities.Abstrak. Krisis ekologis di Teluk Dalam Ambon mencerminkan krisis relasi, etika, dan spiritualitas komunitas iman. Penelitian ini bermaksud mengkaji respons etis jemaat GPM Lateri terhadap degradasi pesisir sejak tahun 2004 dengan menyoroti ketegangan antara pengakuan iman dan praksis ekologis sehari-hari. Penelitian kualitatif ini menggunakan kerangka refleksi teologis kontekstual model praksis-transformatif. Data diperoleh melalui wawancara, observasi, dan analisis dokumen, kemudian dianalisis secara tematik dengan mendialogkannya bersama konsep Stewardship. Temuan menunjukkan dominasi paradigma “manusia di atas alam” serta etika ekologis dangkal. Penelitian ini merekonstruksi Stewardship melalui dialog Humanity with Nature dan nilai Kalesang sebagai model Ekoteologi relasional dan kontekstual bagi masyarakat pesisir perkotaan Indonesia.